A low-complexity enhancement to suboptimal CDMA receivers. - Lau, A.P.T.
Conventional matched-filter detectors for code-division multiple-access (CDMA) systems suffer from multiple-access interference (MAI) caused by nonzero correlation between spreading codes at the receiver. A host of advanced detector structures have been proposed to reduce the effect of MAI and, hence, improve performance. However, most multiuser detectors suffer from their relatively complex implementations. A simple method is proposed to improve the performance of the conventional detector by detecting and correcting decision errors at its output without the use of forward error correcting (FEC) codes. The proposed post-detection error control method is shown to substantially improve the performance of the conventional detector, but has a much lower complexity than most other multiuser detectors.
Keywords: Code-division multiple-access system; Conventional matched-filter detector; Correcting decision error; Forward error correcting code; Multiple-access interference; Multiuser detector; Nonzero correlation; Post-detection error control method; Spreading code; Suboptimal CDMA receiver